Correlation of advanced glycation end products (AGEs) intake with prehypertension incidence among adults - Loriza Sativa Yan (Riset Informasi Kesehatan, 2023)
Background : The incidence of prehypertension in adults has a threefold risk of developing hypertension and triggering heart disease when compared to other ages population. This study aimed to correlate the intake of advanced glycation end products (AGEs) with the incidence of prehypertension in adults in Kota Jambi. Method : A cross-sectional study using the correlation method with a sample of 134 people aged 21 – 59 years who came for treatment at the Tanjung Pinang Public Health Center, Kota Jambi and sample selected by purposive sampling. Data collected by using a questionnaire and analyzed by Spearman rank. Results : a strong relationship between AGEs intake and prehypertension (p = 0.000; r: 0.725) Conclusion AGEs intake has a correlation with the incidence of prehypertension in adults.